Integrative review on sustaining curriculum change in higher education: Implications for nursing education in Africa - Champion N. Nyoni; Yvonne Botma (Elsevier, 2020)
Higher education institutions are driven by various factors to engage in planned curriculum change. Nursing education institutions, which are part of higher education in most countries in Africa, have been engaged in significant nation-wide planned curriculum change for their nursing programmes in the last ten years. These planned curriculum changes have been an output of intensive financial, material, and human resource investments by nursing education institutions, governments, and partner organisations. The complexity of planned curriculum change and subsequent implementation challenges creates a need for effective strategies to sustain such planned curriculum change. The purpose of this integrative review was to synthesise strategies used to sustain planned curriculum change in higher education between January 1997 and September 2017 and reflect implications for nurse education in Africa. Sixteen electronic databases were searched and reference lists checked, citations tracked and journals hand-searched to identify literature reflecting strategies used to sustain planned curriculum changes in higher education. A total of 30 articles were included in this review.Faculty development and involvement, planning, and funding, quality assurance, student involvement, and leadership reinforced the strategies used to sustain planned curriculum change. These strategies were tailor-made to specific role-players within higher education at the various levels of curriculum implementation. We argue that the strategies presented in this article should be used to support and enable the various role players in nursing education in Africa or developing countries to sustain planned curriculum changes.